1986
DOI: 10.1111/j.1476-5381.1986.tb10209.x
|View full text |Cite
|
Sign up to set email alerts
|

BW A256C, a chemically novel class 1 antiarrhythmic agent. A comparison of in vitro and in vivo activity with other class 1 antiarrhythmic agents

Abstract: 1 BW A256C (5(3)-amino-6-(2,3-dichlorophenyl)-2,3(2,5)-dihydro-3(5)-imino-2-isopropyl-1,2,4-triazine) is a novel class 1 antiarrhythmic agent designed to combine the features ofpotency with reduced central nervous system penetration. 2 BW A256C reduced the maximum rate of depolarization of guinea-pig ventricle and dog Purkinje fibres in vitro (EC5o, 2.2 x 10-6 M and 1.8 x 10-6 M, respectively), being significantly more potent than quinidine, lidocaine, disopyramide and flecainide. BW A256C was also more potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Action potential duration and effective refractory period (ERP) are not significantly changed by BW A256C in the guinea pig ventricular muscle. However, in the dog Purkinje fibre both parameters are decreased in a concentration-dependent manner; this is attributable to an effect on the inward "window" current, camed by sodium ions, which contributes to maintenance of the plateau in Purkinje tissue (2,3,8). and 1.8 X Data show mean percentage changes & SEM for GPV (n = 6) and DPF (n = 5).…”
Section: Pharmacological Studies Electrophysiological Studies In Vitromentioning
confidence: 98%
See 4 more Smart Citations
“…Action potential duration and effective refractory period (ERP) are not significantly changed by BW A256C in the guinea pig ventricular muscle. However, in the dog Purkinje fibre both parameters are decreased in a concentration-dependent manner; this is attributable to an effect on the inward "window" current, camed by sodium ions, which contributes to maintenance of the plateau in Purkinje tissue (2,3,8). and 1.8 X Data show mean percentage changes & SEM for GPV (n = 6) and DPF (n = 5).…”
Section: Pharmacological Studies Electrophysiological Studies In Vitromentioning
confidence: 98%
“…However, unlike these agents, BW A256C is devoid of hypotensive activity at antiarrhythmic doses ( Table 4). When BW A256C is compared with flecainide in this preparation, it can be demonstrated that at equieffective antian-hythmic doses there is greater cardiovascular depression, as indicated by a reduction in blood pressure, heart rate, and atrioventricular conduction associated with the administration of flecainide (2).…”
Section: Inhibition Of Aconitine-induced Arrhythmias In Anaesthetisedmentioning
confidence: 99%
See 3 more Smart Citations